Dr. B. R. Ambedkar’s Thoughts on Buddha, War, and Global Peace - Prabhuraj K. Nayaka, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Dr. B. R. Ambedkar thought that Buddhism is an ultimate way to a civilized world order. For a better global order, nonviolence is an ultimate way to civilize society. Dr. Ambedkar thought that, “Before the world, and especially before Asia, only two paths are available today. One is the path of Buddha, the other is the path of Marx. If the world does not adopt Buddha’s philosophy from now on, the victory of Communist Philosophy will become inevitable. Only Buddha’s philosophy is the sole foundation for the world, and to the extent that its spread happens, to that extent the world will move away from war and closer to peace.”
Keywords: Dr. B. R. Ambedkar; Buddhism; Foreign Policy; Democracy vs. Communism; Global Peace